HIDROLISIS ENZIMATIS LIGNOSELULOSA TANDAN KOSONG KELAPA SAWIT MENJADI GULA PEREDUKSI - Maria Bintang; Faizal Gayang; Nur Richana (PROSIDING SEMINAR KIMIA, 2014)
he processing of palm oil into crude palm oil (CPO) produced solid waste such as oil palm empty fruit bunches (OPEFB) with an average of 10 million tons / year which has not been used optimally and can pollute the environment. The main co mponents of OPEFB is cellu lose and lignin called lignocellulose waste. The content of cellulose and hemicellulose in OPEFB potential to be used as a source of reducing sugar by acid hydrolysis or enzyme. Hydrolysis of OPEFB performed using HCl followed by enzy matic hydrolysis using cellulase 0.5% and xy lanase 0.5%. The results showed a reducing sugar level produced with xylanase was 50.5 mg / L and hydrolysis with cellulase was 37.05 mg/L.